Desafíos del constitucionalismo democrático en América Latina. THEMIS Revista de Derecho; Núm. 88 (2025) - Gargarella, Roberto (Pontificia Universidad Católica del Perú, 2025)
This text critically examines the challenges to democratic constitutionalism in Latin America, focusing on the structural tension between the expansion of rights catalogs and the maintenance of a concentrated power structure, particularly within the executive branch. In this regard, the text highlights Latin America’s most significant contributions to global constitutionalism while simultaneously identifying persistent shortcomings in institutional design. These shortcomings have led to a profound gap between normative promises and their actual effectiveness, eroding the legitimacy of the constitutional order. In response, the author proposes rethinking constitutionalism from the perspective of a substantive democracy that is not merely reduced to electoral mechanisms but is understood as a deliberative process between elections.

El texto examina críticamente los desafíos del constitucionalismo democrático en América Latina a partir de la tensión estructural entre la expansión de los catálogos de derechos y el mantenimiento de una organización del poder concentrada, particularmente en el Poder Ejecutivo. En ese sentido, a lo largo de estas líneas se destacan los aportes más relevantes de América Latina al constitucionalismo global, al mismo tiempo que se identifican las deficiencias persistentes en el diseño institucional. Esto último ha dado lugar a una brecha profunda entre las promesas normativas y su efectividad real, erosionando la legitimidad del orden constitucional. Frente a ello, el autor propone repensar el constitucionalismo desde la óptica de una democracia sustantiva que no solo se reduzca a mecanismos electorales, sino que sea entendida como un proceso deliberativo entre elecciones.
Challenges of democratic constitutionalism in Latin America
Keywords: Democratic constitutionalism; Concentrated power; Institutional weakening; Democracy; Crisis of representation; Constitucionalismo democrático; Poder concentrado; Debilitamiento institucional; Democracia; Crisis de representación; https://purl.org/pe-repo/ocde/ford#5.05.01